High Expression of Galectin-1, VEGF and Increased Microvessel Density Are Associated with MELF Pattern in Stage I-III Endometrioid Endometrial Adenocarcinoma - Dmitry Aleksandrovich Zinovkin; Sergey Leonidovich Achinovich; Mikhail Grigoryevich Zubritskiy; Jacqueline Linda Whatmore; Md Zahidul Islam Pranjol (Korean Society of Pathologists & the Korean Society for Cytopathology, 2019)
Background In this study, we investigate the expression of markers of angiogenesis and microvessel density (MVD) in cases of microcystic, elongated and fragmented (MELF) pattern, with its prognostic role in the survival of endometrioid endometrial adenocarcinomas (EA) patients. Methods In this study, 100 cases of EA, 49 cases with MELF pattern and 51 without, were immunohistochemically stained for galectin-1, vascular endothelial growth factor (VEGF), and MVD. Morphometry and statistical (univariate and multivariate) analyses were performed to assess overall survival (OS) and disease-free survival. Results The expression of VEGF (p<.001) and galectin-1 (p<.001), as well as MVD area (p<.001) and number of vessels/mm2 (p<.050), were significantly higher in the +MELF pattern group compared to the -MELF group. A low negative correlation between MELF-pattern and the number of days of survival (p<.001, r=-0.47) was also found. A low positive correlation of MELF-pattern with galectin-1 expression (p<.001, r=0.39), area of vessels/mm2 (p<.001, r=0.36), outcome of EA (p<.001, r=0.42) and VEGF expression (p<.001, r=0.39) suggests potential pathological relevance of these factors in the prognosis of EA. A univariate survival analysis indicated a role for all parameters of survival. Multivariate Cox proportional hazard regression analysis revealed that only area of vessels/mm2 (hazard ratio [HR], 1.018; 95% confidence interval [CI], 1.002 to 1.033), galectin-1 (HR, 1.049; 95% CI, 1.025 to 1.074) and VEGF (HR, 1.049; 95% CI, 1.022 to 1.077) play key roles in OS. Conclusions This study reports an increase in MVD, VEGF and galectin-1 expression in EA with MELF pattern and suggests that MELF pattern, along with the angiogenic profile, may be a prognostic factor in EA.